Legal Protection for Users of Crypto Assets in Futures Exchange Transactions - Fidel, Yohanes; Lastuti Abubakar; Ema Rahmawati (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to understand the form and effectiveness of legal protection for consumers of crypto assets before and after the enactment of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (PPSK Law) and Financial Services Authority Regulations (POJK) Number 27 of 2024 and POJK Number 3 of 2024. The method used is normative legal research with a legislative approach and qualitative descriptive analysis techniques. This approach was chosen to explore the substance of legal norms and assess the practical implications of regulatory changes on the rights of consumers who use crypto assets. The novelty of this research lies in its critical analysis of the changes in the supervisory regime from the perspective of legal protection for digital asset consumers, which has not been comprehensively discussed before. This research is relevant amid the dynamic development of the rapidly evolving and complex digital financial sector, particularly following the enactment of the PPSK Law and the OJK's derivative regulations. The results of the study indicate that prior to the implementation of the latest regulations, legal protection for consumers of crypto assets was minimal and sectoral in nature, with a focus on commodity aspects by BAPPEBTI. This resulted in weak protection against risks such as value fluctuations, fraud, and threats to digital transaction security. However, after being transferred to the OJK, the protection approach became more integrated through the regulation of business licenses, clearing systems, digital asset storage governance, and more adequate dispute resolution mechanisms. In conclusion, the transfer of regulatory authority to the OJK significantly strengthens legal protection for cryptocurrency consumers in Indonesia. The new regulations enhance legal certainty and increase user confidence, while also fostering the development of a more transparent, accountable, and consumer-oriented digital asset ecosystem.